Anti-inflammatory effect of MAPK phosphatase-1 local gene transfer in inflammatory bone loss - Yu, Hong; Li, Qiyan; Herbert, B; Zinna, R.; Martin, K.; Rossa Júnior, Carlos [UNESP]; Kirkwood, K. L. (Springer Nature, 2010)
Alveolar bone loss associated with periodontal diseases is the result of osteoclastogenesis induced by bacterial pathogens. The mitogen-activated protein kinase (MAPK) phosphatase 1 (MKP-1) is a critical negative regulator of immune response as a key phosphatase capable of dephosphorylating activated MAPKs. In this study, rat macrophages transduced with recombinant adenovirus (Ad.)MKP-1 specifically dephosphorylated activated MAPKs induced by lipopolysaccharide (LPS) compared with control cells. Bone marrow macrophages from MKP-1 knockout (KO) mice exhibited higher interleukin (IL)-6, IL-10, tumor necrosis factor (TNF)-α, and select chemokine compared with wild-type (WT) mice when stimulated by LPS. In addition, bone marrow cultures from MKP-1 KO mice exhibited significantly more osteoclastogenesis induced by LPS than when compared with WT mice. Importantly, MKP-1 gene transfer in bone marrow cells of MKP-1 KO mice significantly decreased IL-6, IL-10, TNF-α and chemokine levels, and formed fewer osteoclasts induced by LPS than compared with control group of cells. Furthermore, MKP-1 gene transfer in an experimental periodontal disease model attenuated bone resorption induced by LPS. Histological analysis confirmed that periodontal tissues transduced with Ad. MKP-1 exhibited less infiltrated inflammatory cells, less osteoclasts and less IL-6 than compared with rats of control groups. These studies indicate that MKP-1 is a key therapeutic target to control of inflammation-induced bone loss.